Community first responders: A missing key to reducing the impact of injury and illness in low- and middle-income countries in the Western Pacific? (Western Pacific Surveillance and Response, 2021)
This perspective article discusses the potential role community first responders could play in reducing injury and illness in low- and middle-income countries in the Western Pacific. Community first responders are reportedly making a difference in low- and middle-income countries in Asia and Africa in reducing injury and illness, and in disease surveillance and reporting. Efforts must be made to explore the appropriate and effective introduction of locally tailored community first responder programs in the Western Pacific.